The factors that influence the grocery purchase decisions among young consumers at Kota Bharu - Ahiswarya Thenagopal; Ahmad Zahid Kamarul Zaman; Lai Mae Kwan; Lim Chai Loon (2019)
Purchase decision is the thought process that leads a consumer from identifying a need, generating options, and choosing a specific product and brand. The purpose of the study is based on the factors that influence the grocery purchase decisions among young consumers at Kota Bharu, Kelantan. The objective of this study is to examine the relationship between social media marketing, sales promotion, store environment, price of products and family influence towards young consumer’s grocery purchase decisions. The researcher observed that social media marketing especially Facebook, sales promotion like coupons and “Buy 1 Get 1 Free”, ambience store environment, price and family influences will affect the grocery purchase decisions of young consumers. In order to examine the factors influencing grocery purchase decisions among young consumers at Kota Bharu, this research was designed as a survey using a constructed survey questionnaire to collect data from young consumers at Kota Bharu. There are 400 respondents have been randomly involves in the questionnaire conducted by the researcher. This study focused on the grocery purchase decision among young consumers at Kota Bharu. This research analysed the relationship connection between social media marketing, sales promotion, store environment, price of products and family influence among young consumers at Kota Bharu by using descriptive analysis. The findings of data are essential in order to improve the grocery purchase decision among young consumers at Kota Bharu.